Evaluasi Kebijakan Pemberian Bantuan Pengembangan Usaha Mina Perdesaan di Kabupaten Minahasa Selatan - Tulusan, Femmy; Egeten, Maxi; Lintjewas, Olga Y L (JURNAL ILMIAH SOCIETY, 2016)
The aim of this study "Evaluating Policy Assistance Mina Rural Enterprise Development (PUMP) in South Minahasa Regency". This study used a qualitative approach with descriptive analysis method. Sources of primary data obtained through interviews with a purposive sampling techniques and secondary data from documents, files, internet, and other sources associated with the research. The survey results revealed Implementation Program Direct Community Assistance (BLM) Mina Rural Enterprise Development (PUMP) in South Minahasa Regency has gone well. All processes are carried out in compliance guidelines. All of these mechanisms have been implemented according to their respective authorities ranging from the establishment of a technical team to the receiver group selection. Since the program was rolled in South Minahasa Regency (years 2011-2015), as many as 73 groups have received this assistance and has been used for business development in the field of fisheries, aquaculture, processing and marketing of fishery products. Implementation of this program has had an impact on the implementation of this program. The perceived impact of fish production increased compared to before receiving this assistance. Likewise with income, an increase when compared with the initial conditions before granting aid.